Development of a microplate-based novel toxicity bioassay using Chlorophyta and Phaeophyceae macroalgae - Onduka, Toshimitsu; Somiya, Rei; Yamagishi, Takahiro; Hano, Takeshi; Yamamoto, Hiroshi; Mochida, Kazuhiko (Ecotoxicology (London), 2023)
Macroalgae are one of the main producers in marine environments. However, only a few toxicity test methods have been established that use reference strains of macroalgae to evaluate the effects of chemicals on the growth and reproduction of macroalgae to monitor water quality. We selected reference strains of Chlorophyta, Ulva aragoënsis ; Phaeophyceae, Ectocarpus siliculosus ; and wakame, Undaria pinnatifida , as test species to establish a microplate-based method to investigate the toxicity of potassium dichromate, 3,5-dichlorophenol, and two common herbicides (diuron and simazine). We determined the growth of the three macroalgae in their early life stages and during the sporangia formation stage in E. siliculosus under laboratory conditions. We observed that the growth and sporangia formation in these algae were impaired in a dose-dependent manner. Additionally, we investigated the sensitivity of these macroalgae by comparing the toxicity values of toxicants used in this study with those obtained from a database. Compared to other microalgae and plant species, macroalgae showed a relatively high sensitivity to organic compounds, including herbicides. Growth tests using U. aragoënsis and E. siliculosus produced reliable results at 0–32 and 25–32 practical salinity units (PSU), respectively. The tests established in this study could test the toxicity of chemical substances in macroalgae and are thus expected to contribute to a better understanding of the environmental risks of chemical substances on aquatic biota. The tests could be applied to all effluent toxicity tests used for the management of seawater and brackish water quality.